Microarchitecture of Schlemm Canal Before and After Cataract Extraction Surgery. Issue 8 (August 2019) - Rubinstein, Yair; Fogel-Levin, Miri; Singer, Reut; Levkovitch-Verbin, Hani; Moros, Iris; Sher, Ifat; Rotenstreich, Ygal; Skaat, Alon
Abstract : Precis: Schlemm canal (SC) expands after cataract extraction (CE), both in the area and in volume by 25% as was measured using enhanced-depth imaging optical coherent tomography (EDI-OCT) in patients before and 1 week after CE. Purpose: This study aims to characterize the structural and volume changes on the microstructure of SC in patients before and after uneventful phacoemulsification CE by using EDI-OCT. Materials and Methods: Forty-one serial horizontal EDI-OCT B-scans (interval between B-scans, 69 µm) were obtained in the nasal corneoscleral limbus before and 1 week after CE. The structure of aqueous channels, conjunctival blood vessels and iris anatomy in each scan were used as landmarks to select for overlapping scans taken before and following CE. The SC cross-section area was measured in each of the selected scans and SC volume was determined following a 3-dimensional reconstruction. Results: Eleven eyes (6 females and 5 males) were imaged successfully before and after CE. Mean age was 70.54±11.38 years. The mean axial length was 23.10±0.87 mm. After CE, the mean best-corrected visual acuity in logMAR improved from 0.4±0.13 to 0.2±0.13 ( P =0.028). There was no significant change in the mean intraocular pressure before and after CE (15.09±1.33 to 15.0±2.16 mm Hg; P =0.39). The mean SC cross-section area increased by 25%, from 4744±376 to 5941±1048 μm 2 ( P <0.001). SC volume in the analyzed region increased by 25% from 6, 641, 473±585, 954 to 8, 317, 909±1, 328, 809 μm 3 ( P <0.001). Conclusion: CE expands SC dimensions in healthy eyes. EDI-OCT imaging of SC may prove useful in the evaluation of the SC dimensions in vivo before and after CE. Abstract : Supplemental Digital Content is available in the text.